Controlling strong-field fragmentation of H2+ by temporal effects with few-cycle laser pulses - McKenna, J.; Anis, F.; Sayler, A. M.; Gaire, B.; Johnson, Nora G.; Parke, E.; Carnes, K. D.; Esry, B. D.; Ben-Itzhak, I. (My University, 2012)
In a joint experimental and theoretical endeavor, we explore the laser-induced dissociation and ionization dynamics of H2+ beams using sub-10-fs, 800 nm laser pulses. Our theory predicts considerable control over the branching ratio of two-photon and three-photon above-threshold dissociation (ATD) by gating the dissociation pathway on a few-femtosecond timescale. We are able to experimentally demonstrate this control. Moreover, our theory also shows the importance of the highly excited H(2l) states of H2+ that contribute to ATD structure in dissociation. As is the case for dissociation, we find that ionization is also sensitive to the effective laser interaction time.